Intracholecystic papillary neoplasm (ICPN) of gallbladder. a case report - Mohd Ali, Razana; Azman, Sue Anida; Mohtarrudin, Norhafizah (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2024)
In the WHO Classification of Tumours of the Digestive System (2019), intracholecystic papillary neoplasm (ICPN), a pre-invasive neoplasm of the gallbladder, is described as non-invasive epithelial neoplasm with macroscopically discernible mass of pure papillary, tubular or tubulo-papillary architecture. The mass-forming characteristic of ICPNs in the gallbladder is radiologically similar to that of invasive tumours. Case report: A 58-year-old man presented with vomiting and prickling epigastric pain for two days. An abdominal CT scan showed a gallbladder tumour associated with dilated intrahepatic and common bile ducts. A wide-base polypoid tumour with papillary surface projection of 30 x 20 x 10 mm dimensions was present. Microscopically, a tubulo-papillary glandular tumour with high grade dysplastic foci and glandular areas with prominent intracellular mucin was seen. The adjacent mucosa displayed features of chronic cholecystitis, including pyloric metaplasia. After thorough sampling, there was no evidence of muscle infiltration, architectural complexity or perineural invasion. A diagnosis of intracholecystic papillary neoplasm with high grade dysplasia of the gallbladder was made. Discussion: The incidence of pre-invasive gallbladder neoplasms such as ICPN is less than 1% in a few studies, making them quite uncommon. It might be mistakenly identified radiographically as an invasive malignancy since it is forming a mass. In ICPN, the increase prevalence of diffuse high-grade dysplasia, papillary architecture, and biliary phenotype are linked to an increased risk of invasive malignancy. Nevertheless, gallbladder carcinoma with ICPN has better prognosis than those without.